Comparative Studies of Mesial Temporal Lobe Epilepsy with Epilepsy from Brain Tumors - Rajesh Kumar Kar (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
Mesial temporal lobe epilepsy (MTLE) and epilepsy associated with brain tumors (EABT) are two distinct forms of epilepsy with unique etiologies and clinical manifestations. This comparative study aims to explore the similarities and differences between these two epilepsy conditions, shedding light on their underlying mechanisms, clinical characteristics, and treatment approaches. Comparative analysis reveals several commonalities in the pathophysiology of MTLE and epilepsy from brain tumors. Both conditions involve alterations in cellular metabolism, disruptions in neuronal networks, and neuroinflammatory processes. Metabolic dysregulation, such as glucose metabolism abnormalities and mitochondrial dysfunction, is observed in both MTLE and tumor-related epilepsy. Additionally, shared molecular pathways related to excitotoxicity, synaptic plasticity, and inflammation contribute to epileptogenesis in both conditions. However, notable differences are also observed. MTLE primarily affects the mesial temporal lobe structures, particularly the hippocampus, while brain tumor-related epilepsy (BTRE) is associated with structural abnormalities resulting from tumor growth. These structural differences influence the clinical presentations, seizure types, and response to antiepileptic drugs. Furthermore, molecular heterogeneity is more pronounced in BTRE, reflecting the diverse molecular subtypes of brain tumors and their distinct effects on epileptogenesis. The comparative analysis also explores the implications for treatment approaches. While antiepileptic drugs are the primary treatment option for both conditions, surgical interventions, including resective surgery and tumor removal, play a more prominent role in BTRE. Moreover, understanding the differences in treatment response and prognosis between the two conditions can aid in personalized treatment planning and optimize patient care. In conclusion, this comparative study highlights the shared and distinct features of MTLE and epilepsy from brain tumors, deepening our understanding of their underlying mechanisms and clinical characteristics. The findings have significant implications for accurate diagnosis, tailored treatment strategies, and improved outcomes for patients with these epilepsy conditions. Further research is warranted to unravel the complexities of both conditions and explore novel therapeutic avenues for effective seizure control and disease management.